Development and Reliability of the Basic Skill Assessment Tool for Adolescents with Autism Spectrum Disorder - Maethisa Pongsaksri (2018)
© 2017 Maethisa Pongsaksri et al. The purpose of this study was to improve upon the first version of the basic work skills assessment tool for adolescents with autism spectrum disorder (ASD) and examine interrater and intrarater reliability using Intraclass Correlation Coefficient (ICC). The modified tool includes 2 components: (1) three tasks measuring work abilities and work attitudes and (2) a form to record the number of verbal and nonverbal prompts. 26 participants were selected by purposive sampling and divided into 3 groups - group 1 (10 subjects, aged 11-13 years), group 2 (10, aged 14-16 years), and group 3 (6, aged 17-19 years). The results show that interrater reliabilities of work abilities and work attitudes were high in all groups except that the work attitude in group 1 was moderate. Intrarater reliabilities of work abilities in group 1 and group 2 were high. Group 3 was moderate. Intrarater reliabilities of work attitudes in group 1 and group 3 were high but not in group 2 in which they were moderate. Nevertheless, interrater and intrarater reliabilities in the total scores of all groups were high, which implies that this tool is applicable for adolescents aged 11-19 years with consideration of relevance for each group.